The light Of ALLAH: Quran stories of little heart - Khan Saniyasnain (India: Goodwordkidz, 2011)
The Light of the Quran" explores the teachings, themes, and wisdom found within the Quran. It emphasizes the Quran's role as a guide for personal development, spirituality, and ethical living. The book delves into various concepts such as justice, compassion, and the importance of faith, while also addressing contemporary issues and the relevance of the Quran in today's world. Through insightful interpretations and reflections, it aims to illuminate the transformative power of the Quran for individuals and communities alike.
Keywords: English-text